2018
DOI: 10.1111/1750-3841.14112
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Transport Mechanism of Dihydromyricetin Across Human Intestinal Caco‐2 Cells

Abstract: This study elucidated the uptake and transport characteristics of dihydromyricetin (DMY). DMY was poorly absorbed by a passive diffusion mechanism. The uptake and transport of DMY were time and concentration dependent. Interestingly, pH affected DMY uptake but not its bidirectional transport. MRP2 and BCRP were involved in the uptake and transport of DMY, which hindered the absorption of DMY in the intestinal. Thus, the present study may provide useful information for designing DMY delivery systems and avoidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…However, little information is available on DMY's absorption profiles, distribution, metabolism, and excretion in animal models and in human body. In a recent study (Xiang et al, 2018), a human intestinal Caco-2 cell model was used to investigate the uptake and transport mechanism of DMY. The effect of time, concentration, pH, temperature and efflux transporters on its uptake and transport were systematically evaluated.…”
Section: Absorption Metabolism and Elimination Of Dmymentioning
confidence: 99%
See 1 more Smart Citation
“…However, little information is available on DMY's absorption profiles, distribution, metabolism, and excretion in animal models and in human body. In a recent study (Xiang et al, 2018), a human intestinal Caco-2 cell model was used to investigate the uptake and transport mechanism of DMY. The effect of time, concentration, pH, temperature and efflux transporters on its uptake and transport were systematically evaluated.…”
Section: Absorption Metabolism and Elimination Of Dmymentioning
confidence: 99%
“…In addition, the pharmacokinetic characteristics of DMY in animal models and human body are also vital to the evaluation of their in vivo bioavailability efficacy. However, only partial information (Fan, Tong, & Dong, 2017;Xiang, Fan, & Hou, 2018;Zhang et al, 2007) is available on basic pharmacokinetic studies of DMY such as absorption, distribution, metabolism and excretion in organisms, biotransformation processes and metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma DHM concentration reached maximum (159 μg/L) at 1.5 h postadministration when DHM powder was given at a dosage of 115 mg/kg body weight in rabbits, indicating a low bioavailability of DHM [18]. Efflux transporters, multidrug resistance protein 2, and breast cancer resistance protein also played an important role in DHM uptake and transport processes [22]. A research group had investigated the distribution, excretion, and metabolic profile of DHM and found that most unconverted DHM forms were excreted in feces [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the time required for it reaches peak plasma concentration is 2.67 h after oral administration at a dose of 20 mg/kg (Liu et al, 2017). A recent in vitro study using the human intestinal Caco-2 cell model, a common tool used to predict, in vivo , the absorption of drugs in humans, showed that the uptake and transport of DHM occurs mainly through a passive diffusion mechanism, which can partially explain the low bioavailability of DHM after oral administration (Xiang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%